Parity violation in the compound nucleus - Mitchell, Gary; Bowman, J. David; Weidenmüller, Hans-Arwed (Reviews of modern physics, 1999)
Parity violation in the compound nucleus is reviewed as an example of a wider class of phenomena: The breaking of a discrete symmetry by a weak interaction in a stochastic or chaotic quantum system. Generically, enhancement factors amplify the signal for symmetry breaking, and the stochastic properties allow the strength of the symmetry-breaking interaction to be inferred from that signal without the need to know the wave functions of individual states. We describe recent experiments on parity violation that have been undertaken in this spirit. The scattering of spin-polarized neutrons by medium-weight and heavy nuclei provides signals for parity violation at the percent level. The statistical analysis of the data yields values for the spreading width around 10−6eV, in keeping with theoretical expectations. We discuss open problems and possible future directions.
Gesehen am 01.12.2020